On the vertical phytoplankton response to an ice‐free Arctic Ocean. Issue 12 (31st December 2015) - Lawrence, J.; Popova, E.; Yool, A.; Srokosz, M.
Abstract: Rapidly retreating sea ice is expected to influence future phytoplankton production in the Arctic Ocean by perturbing nutrient and light fields, but poor understanding of present phytoplankton distributions and governing mechanisms make projected changes highly uncertain. Here we use a simulation that reproduces observed seasonal phytoplankton chlorophyll distributions and annual nitrate to hypothesize that surface nitrate limitation in the Arctic Ocean deepens vertical production distributions where light‐dependent growth rates are lower. We extend this to interpret depth‐integrated production changes projected by the simulation for an ice‐free Arctic Ocean. Future spatial changes correspond to patterns of reduced surface nitrate and increased light. Surface nitrate inventory reductions in the Beaufort Gyre and Atlantic inflow waters drive colocated production distributions deeper to where light is lower, offsetting increases in light over the water column due to reduced ice cover and thickness. Modest production increases arise, 10% in a seasonally ice‐free Arctic Ocean and increasing to 30% by the end of the century, occurring at depth. Key Points: We use a 1/4° ocean biogeochemical model to assess Arctic primary production Net primary production is linked to nitrate‐light conditions Application to future production suggests modest increases, occurring at depth